2020
DOI: 10.3389/fonc.2019.01488
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and Risk Factors of Radiation-Induced Lymphopenia in Early-Stage Lung Cancer Treated With Stereotactic Body Radiation Therapy

Abstract: Background: To investigate the role of stereotactic body RT (SBRT) in decreased total peripheral lymphocyte count (TLC) in patients with early-stage lung cancer and to explore possible risk factors for RT-induced lymphopenia. Materials and Methods:We analyzed the TLCs and lymphocyte subsets of 76 patients in our prospective clinical database who received SBRT for early-stage lung cancer treatment. Relationships between clinical factors or dosimetric parameters and TLC were evaluated using Spearman's correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 32 publications
2
12
1
Order By: Relevance
“…Our results suggest that SBRT may not induce clinically meaningful RIL despite the associated risk of a large volume of healthy lung receiving low-dose spillage. Our results differ from those recently published by Zhao et al, where RIL was associated with both lower PFS and OS in patients treated with SBRT for early stage NSCLC [ 17 ]. One major explanatory difference lies in the timing of lymphocyte collection, with Zhao’s analysis focusing on lymphocyte counts collected within a week of SBRT completion and this analysis focusing on a period of up to 6 months post-treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results suggest that SBRT may not induce clinically meaningful RIL despite the associated risk of a large volume of healthy lung receiving low-dose spillage. Our results differ from those recently published by Zhao et al, where RIL was associated with both lower PFS and OS in patients treated with SBRT for early stage NSCLC [ 17 ]. One major explanatory difference lies in the timing of lymphocyte collection, with Zhao’s analysis focusing on lymphocyte counts collected within a week of SBRT completion and this analysis focusing on a period of up to 6 months post-treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…For the contribution of irradiation volume at heart, our findings are consistent with our previous study in lung cancer patients, i.e. higher heart V5 (the heart volume in 5Gy) was significant with decrease in post-radiation lymphocyte counts (31). The results of these studies were all consistent with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Considering the impact of irradiation dose on lymphopenia, the contribution of integral dose of the total body also has been presented in our previous work of EDIC formula containing integral dose of the total body resulted lymphopenia in 488 esophageal cancer patients ( 29 ); V5 of ipsilateral lung/bilateral lungs have been previously reported to impact lymphopenia in non-small cell lung cancer patients ( 30 ). Similar findings have been reported in patients with early-stage lung cancer, V10 to V50 were significantly negatively correlated with the decrease of absolute lymphocyte counts following radiation ( 31 ). In patients with pancreatic cancer, V10, V15, and V20 were significantly higher in patients with severe lymphopenia ( 32 ), and the same findings in patients with esophageal squamous cell carcinoma ( 33 ).…”
Section: Discussionsupporting
confidence: 87%
“…An experimental canine study demonstrated that the number of lymphocytes in the peripheral blood decreases after TBI or TLI procedures (Storb et al., 1999). In a previous clinical study, a subset analysis of peripheral blood lymphocytes in human patients after radiation therapy was performed, and the authors reported that the levels of B‐ and T‐helper lymphocytes significantly decreased compared with those of other lymphocytes (Zhao et al., 2020). The human and veterinary clinical studies described a reduction in the levels of peripheral blood lymphocytes with localized radiotherapy (Belka et al., 1999; Kent et al., 2020).…”
Section: Discussionmentioning
confidence: 99%